2015
DOI: 10.1002/2015gl066043
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced carbon dioxide causing the dust storm‐related increase in high‐altitude photoelectron fluxes at Mars

Abstract: Several studies have shown that the Martian global dust storm occurred in 2001 had a long‐term influence on high‐altitude photoelectron fluxes by analyzing the observations of the magnetometer/electron reflectometer instrument on board Mars Global Surveyor, most likely because the dust altered the neutral atmosphere in a significant way in terms of photoelectron production and loss. This study investigates candidate atmospheres that can replicate observations, especially focusing on the role that thermospheric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 46 publications
0
25
0
Order By: Relevance
“…Our simulation, shown in Figure , perfectly reproduced this phenomenon. In fact, according to recent observations, the increase of neutral density in Martian upper atmosphere can significantly increase the photoelectron flux across all energy ranges (Xu et al, ); therefore, the lift of the upper ionosphere may also be related to the variations of neutral density, especially the variations of CO 2 density, which is the main source of the electrons in this region (Wang & Nielsen, ). The latest observations of MAVEN have strongly demonstrated the obvious increase of CO 2 density between 170 and 220 km during dust storms (Liu et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our simulation, shown in Figure , perfectly reproduced this phenomenon. In fact, according to recent observations, the increase of neutral density in Martian upper atmosphere can significantly increase the photoelectron flux across all energy ranges (Xu et al, ); therefore, the lift of the upper ionosphere may also be related to the variations of neutral density, especially the variations of CO 2 density, which is the main source of the electrons in this region (Wang & Nielsen, ). The latest observations of MAVEN have strongly demonstrated the obvious increase of CO 2 density between 170 and 220 km during dust storms (Liu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Liu et al () even found that the thermosphere (170–220 km) moved upward by about 10 km during a regional storm, which also suggests that the lift of upper ionosphere may be influenced by the lift of neutral atmosphere. According to Xu et al (), the levels where CO 2 density increases during dust storms can extend up to 400 km. The confirmation of extreme height of dust impact on the neutral atmosphere and ionosphere needs further observational data from Mars missions such as MAVEN and Mars Express.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of the other parameters—EUV, SZAm and LT—is less clear and depends on the frame considered (for the LT influence in MSO versus MSE) or on cross‐correlations biases with the major drivers (for SZA near noon, as detailed above), even if the risks of artificial correlations as determined from Fisher's tests are always below 1%, except for the SZA influence (risk of ≈2%). Regarding the EUV influence, we point out that if EUV is a major driver for the photoelectron fluxes (Trantham et al, ; Xu et al, ) through the production mechanisms, its influence on the PEB should be less strong (e.g., the MGS data could not see any EUV influence on the ionopause, Mitchell et al, ). The EUV influence corresponds to an enhanced thermal pressure that will act against the solar wind confinement and thus push the draping of the IMF.…”
Section: The Parameters Of Influence For the Peb: Solar Wind Dynamic mentioning
confidence: 94%
“…At the 400‐km MGS altitude, well above the collisional atmosphere, 10‐eV to 20‐keV electrons are typically magnetized (with a guiding center motion following the magnetic field line), so these electrons serve as excellent magnetic field tracers. As noted in previous studies (e.g., Brain et al, ; Xu, Fang, et al, ), magnetic topology inferred from superthermal electron observations is defined with respect to the suprathermal electron exobase (∼160 km, Xu, Liemohn, Bougher, et al, ; Xu, Liemohn, et al, ), or the foot point(s) of a field line, in lieu of the planet surface, only above which can suprathermal electrons move freely and be used to infer topology. Therefore, in this study, a closed field line is defined as both foot points of a field line embedded in the collisional atmosphere; an open field line is defined as one foot point embedded in the collisional atmosphere and the other connected to the solar wind; a draped field line does not intersect the superthermal electron exobase on either end.…”
Section: Methodsmentioning
confidence: 99%